Does COVID-19 pose a threat for patients after univentricular palliation? Thrombosis of the Fontan tunnel - Jičínská, Denisa; Jičínský, Michal; Koubský, Karel (Cardiology in the young, 2022)
A 6-year-old boy, born with hypoplastic left heart syndrome, underwent total cavopulmonary connection and later presented in a significantly deteriorated condition. A CT scan revealed multiple thrombi in the extracardiac conduit, although the patient was maintained on an effective anticoagulant therapy. Further examination revealed anamnestic antibodies suggesting that the patient had gone through a clinically inapparent COVID-19 infection, which we conclude most likely contributed to his hypercoagulable state and led to the formation of significant thrombi impairing the patient's haemodynamics. The patient underwent a surgical thrombectomy; there were no post-operative thrombotic complications.
Keywords: dítě; Fontanova operace; Fontan Procedure; trombóza; Postoperative Complications; lidé; COVID-19; Male; Humans; Hypoplastic Left Heart Syndrome; pooperační komplikace; Anticoagulants; syndrom hypoplazie levého srdce; antikoagulancia; mužské pohlaví; Child; Thrombosis